2017
DOI: 10.1194/jlr.m078220
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C-III inhibits triglyceride hydrolysis by GPIHBP1-bound LPL

Abstract: apoC-III is often assumed to retard the intravascular processing of triglyceride-rich lipoproteins (TRLs) by inhibiting LPL, but that view is based largely on studies of free LPL. We now recognize that intravascular LPL is neither free nor loosely bound, but instead is tightly bound to glycosylphosphatidylinositol-anchored HDL-binding protein 1 (GPIHBP1) on endothelial cells. Here, we revisited the effects of apoC-III on LPL, focusing on apoC-III's capacity to affect the activity of GPIHBP1-bound LPL. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 36 publications
(35 reference statements)
1
37
0
Order By: Relevance
“…Subsequently, we compared the serum levels of TG and VLDL in HBV patients and normal controls and found that the serum levels of TG and VLDL were lower in HBV patients. ApoC3 is a lipoprotein lipase (LPL) inhibitor, which can inhibit the activities of lipase, hepatic lipase and lecithin cholesterol acyltransferase to affect lipid metabolism [ 27 , 28 ]. LPL is a key enzyme in the catabolism of triglyceride lipoprotein (TRL) [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we compared the serum levels of TG and VLDL in HBV patients and normal controls and found that the serum levels of TG and VLDL were lower in HBV patients. ApoC3 is a lipoprotein lipase (LPL) inhibitor, which can inhibit the activities of lipase, hepatic lipase and lecithin cholesterol acyltransferase to affect lipid metabolism [ 27 , 28 ]. LPL is a key enzyme in the catabolism of triglyceride lipoprotein (TRL) [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…suggesting that the higher LPL activity in BAT during cold exposure (35,36) outweighs the ability of apoC-III to limit LPL accessibility to triglyceride substrates (33,34). We also examined mice deficient in both apoC-III and GPIHBP1 (Gpihbp1 −/− Apoc3 −/− ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in humans have convincingly demonstrated that APOC3 loss-of-function mutations lower TRL levels and offer cardioprotection (15)(16)(17)(18)(19)(20). APOC3 was long believed to elevate plasma TRL levels by inhibiting lipoprotein lipase (14,21), but a human antisense oligonucleotide (ASO) therapeutic against APOC3 markedly reduced triglyceride (TG) levels in lipoprotein lipase-deficient humans with severe hypertriglyceridemia (22). quantified by targeted mass spectrometry (MS).…”
Section: Introductionmentioning
confidence: 99%